Implementation of Reading Aloud Strategy to Improve Students' Reading Skills in Indonesian Language Learning at SMP Negeri 1 Woyla - Musliadi (MANDAILING GLOBAL EDUKASIA, 2025)
This study examines the implementation of the Reading Aloud strategy to improve the reading skills of eighth-grade students at SMP Negeri 1 Woyla. The research was motivated by the observation that many students encounter difficulties in reading fluently and comprehending Indonesian texts, which negatively affects their academic performance. The study employed a classroom action research design carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were 30 students of class VIII, who actively engaged in reading aloud activities designed to enhance pronunciation, intonation, fluency, and comprehension. Data were collected using observation sheets, performance assessments, and teacher field notes. The results showed that the Reading Aloud strategy significantly improved students’ reading ability. In the first cycle, only a limited number of students achieved the minimum fluency and comprehension criteria, while the majority still faced challenges. After adjustments in teacher guidance and reading practice, cycle II demonstrated a substantial increase in performance. Students became more confident in reading aloud, their pronunciation and intonation improved, and comprehension scores rose markedly. The findings indicate that Reading Aloud is an effective strategy to support reading skill development in Indonesian language learning. Therefore, this strategy is recommended for teachers seeking to improve students’ fluency and comprehension through engaging and interactive classroom activities.